Di dèi, umani e galline. Coltivare intimità per vivere con le ferite di Gaia - Guglielmo, Alessandro (AM. Rivista della Società Italiana di Antropologia Medica, 2021)
Of Gods, Humans, and Chickens: Cultivating Intimacy to Live with Gaia’s Wounds. Through this essay, I will explore the ethicopolitical trajectories of the capacity for intimacy. Such capacity has already been observed in the context of Christian charismatic practices and is considered to be engrained in the constitution of a “Sacred Self”. It has also been observed as constituting embodied models of intersubjective encounter. Using my fieldwork experience in a Non-Traditional Modern Advaita sanctuary, a spiritual school based on non-duality, I will observe this capacity outside of the individual boundaries, thus constituting models for relating with the world. Therefore, I will show how the capacity for intimacy can shape embodied care processes in an interspecific framework. Di dèi, umani e galline: coltivare intimità per vivere con le ferite di Gaia. Attraverso questo articolo delineo le possibilità eticopolitiche della capacità di intimità.Tale capacità, già osservata nel contesto delle pratiche cristiane carismatiche, è considerata connaturata alla costituzione di un “Sacred Self”, ed è stata osservata come costituente modelli incorporati di incontro intersoggettivo. Sfruttando la mia esperienza di campo in un santuario Non-Traditional Modern Advaita, una scuola spirituale basata sulla non dualità, osserverò tale capacità esplodere dai confini individuali costituendo modelli di relazione con il mondo. Mostrerò così come la capacità di intimità possa plasmare processi di cura incorporati a livello interspecifico.